Democracy and Foreign Policy in an Era of Uncertainty
XVII, 282 p. 6 illus., 5 illus. in color.
Keywords: In 1995, just a few years into the third wave of global democratic expansion, Maxwell Cameron, and Maureen Appel Molot curated a Canada Among Nations edition on democracy and foreign policy. An organizing premise was that ‘democracy matters as a principle and process in foreign policy; democracies make foreign policy differently and they make different foreign policies.’ Thirty years later, this edition of Canada Among Nations looks back on Canada’s approach to encouraging democracy abroad . Looking ahead the volume considers ways to enhance democracy statecraft in an era of growing international and domestic insecurity, backsliding and populism. Contributors identify patterns and recurring themes in Canadian support for rights and democracy with focus on global trends as well as regional, national, and local processes. Maxwell A. Cameron is Professor, Department of Political Science, School of Public Policy and Global Affairs, the University of British Columbia. David Carment is Professor of International Affairs at the Norman Paterson School of International Affairs, Carleton University. David Gillies has worked at Global Affairs Canada and the Canadian International Development Agency with field postings in Pakistan and Zimbabwe. He has also worked at Rights and Democracy, the Aga Khan Foundation, and the North South Institute.